(untitled) (Romanian Biotechnological Letters, 2024)
The impact on the environment, disregarding the industry is constant. The implications are various out of which the energy sector stands out due to its ability to help reduce the climate change effect. Renewable energies can constitute a necessary change in some domains due to their high environmental impact. Thus, in this paper, the link between renewable energy and the leather industry is highlighted through a bibliometric analysis of the scientific community research.